The Effect of Corporate Social Responsibility and Green Marketing on Purchase Decisions of Cosmetic Products: The Mediating Role of Brand Image - Yoke Levana Hartono; Arthur Sitaniapessy; Joko Rizkie Widokarti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The cosmetics sector in Indonesia has been witnessing significant expansion, driven by a growing consumer consciousness toward sustainability and social accountability. Within this evolving landscape, companies increasingly turn to Corporate Social Responsibility (CSR) initiatives and eco-friendly marketing efforts as key strategies to enhance brand reputation and sway consumer buying behavior. This research explores the interconnection between CSR, green marketing, and consumer purchasing intent in the cosmetics domain. The study focuses on individuals in Tanjungpinang who use products like Avoskin, Hanasui, Makeover, Somethinc, and Wardah. Employing a Partial Least Squares (PLS) approach, the research gathered quantitative data via an online survey and analyzed it using SmartPLS software for thorough and reliable insights. The outcomes of this study offer valuable implications for cosmetic brands aiming to boost purchase intentions by reinforcing their commitment to sustainable practices and CSR, while also contributing to academic discussions on brand perception in the context of green marketing and corporate responsibility.